Aproximación a los esquemas REDD+ en Colombia. Una visión desde su potencial de inclusión social y mejora ambiental (2014)
REDD + schemes for Reducing Emissions from Deforestation and Forest Degradation are an initiative that seeks the establishment of a special incentive for developing countries to protect and manage sustainably their forest resources, contributing to climate change mitigation. From a document qualitative analysis, the article focuses on analyzing the potential of such schemes to encourage sustainability in Colombia, with the central axis of the reflection, the possibility of generating social and environmental co -benefits, with emphasis on the former. As a result a succinct description of three schemes of innovative social business which in turn fit the purposes of REDD + strategies is presented, and that are considered could be implemented in Colombia.